Addressing Non-International Armed Conflicts Vis-À-Vis International Humanitarian Law and Human Rights Regime - Fahim, Md. Hasnath Kabir; Chowdhury, Mohammad Aktarul Alam (Jurnal Hukum dan Peradilan, 2023)
In contrast to traditional wars fought between States, most armed conflicts under international law have been fought within the boundary of States. Non-international armed conflicts (NIAC) are those internal wars or armed conflicts that occur inside the border of a State and include conflict between the government of a State and armed groups or only between armed organizations. Since these internal armed conflicts mirrored war between States in nearly every way, a need arose for a set of laws that might put efforts to 'humanize' their conduct at the same level as the laws regulating international armed conflict (IAC). This article highlights the significant debate between international and non-international armed conflicts and whether the difference has been virtually removed. This paper then discusses how NIAC is governed by the body of laws known as international humanitarian law (IHL). Lastly, this research looks at the debate on the difference between international and non-international armed conflicts from the standpoint of international human rights law (IHRL) to understand the characterization of armed conflicts under IHL. Indeed, there is a great deal of ambiguity in borderline circumstances due to the sliding scale for applying IHL and IHRL in NIAC, which also imposes differing obligations on the government and armed groups. Adopting a harmonious and cooperative approach may prevent any detrimental effects on the development of IHL and IHRL.